Seroprevalence of SARS-CoV-2 in urban settings in three sub-Saharan African countries (SeroCoV): a study protocol for a household-based cross-sectional prevalence study using two-stage cluster sampling - Lorenz, Eva; Souares-Coutant, Aurélia; Amuasi, John; Loag, Wibke; Deschermeier, Christina; Fusco, Daniela; Benke, Dominik; Rakotoarivelo, Rivo A.; Rasamoelina, Mandranto Tahinamandranto; Rakotozandrindrainy, Raphael; Sie, Ali; Awuah, Anthony Afum-Adjei; et al. (BMJ open, 2021)
Introduction The current COVID-19 pandemic has impacted the entire world with increasing morbidity and mortality and has resulted in serious economic and social consequences. Assessing the burden of COVID-19 is essential for developing efficient pandemic preparedness and response strategies and for determining the impact of implemented control measures. Population-based seroprevalence surveys are critical to estimate infection rates, monitor the progression of the epidemic and to allow for the identification of persons exposed to the infection who may either have been asymptomatic or were never tested. This is especially important for countries where effective testing and tracking systems could not be established and where non-severe cases or under-reported deaths might have blurred the true burden of COVID-19. Most seroprevalence surveys performed in sub-Saharan Africa have targeted specific high risk or more easily accessible populations such as healthcare workers or blood donors, and household-based estimates are rarely available. Here, we present the study protocol for a SARS-CoV-2 seroprevalence estimation in the general population of Burkina Faso, Ghana and Madagascar in 2021. - Methods and analysis The SeroCoV study is a household-based cross-sectional prevalence investigation in persons aged 10 years and older living in urban areas in six cities using a two-stage geographical cluster sampling method stratified by age and sex. The presence of anti-SARS-CoV-2 IgG antibodies will be determined using a sensitive and specific SARS-CoV-2 IgG ELISA. In addition, questionnaires will cover sociodemographic information, episodes of diseases and history of testing and treatment for COVID-like symptoms, travel history and safety measures. We will estimate the seroprevalence of SARS-CoV-2, taking into account test performance and adjusting for the age and sex of the respective populations. - Ethics and dissemination Ethical approval was received for all participating countries. Results will be disseminated through reports and presentations at the country level as well as peer-reviewed publications and international scientific conferences presentations.